A Computer Model of the Evaporator and Its Sensors; Chemical Engineering Transactions; Vol. 61 - Chursin Yu. A. Yuri Alexandrovich; Efremov E. V. Evgeny Viktorovich; Gozhimov A. I. Aleksandr Igorevich; Kabrysheva O. P. Oksana Pavlovna; Barkov D. E. Daniil Evgenjevich (2017, 2017)
Title screen